2022
DOI: 10.1007/s12011-022-03197-4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Whole Blood and Urine Trace Elements in Children with Autism Spectrum Disorders and Autistic Behaviors

Abstract: The relationship between trace elements and neurological development is an emerging research focus. We performed a case–control study to explore (1) the differences of 13 trace elements chromium (Cr), manganese (Mn), cobalt (Co), zinc (Zn), arsenic (As), selenium (Se), molybdenum (Mo), cadmium (Cd), stannum (Sn), stibium (Sb), mercury (Hg), titanium (TI), and plumbum (Pb) concentration in whole blood and urine between autism spectrum disorder (ASD) children and their typical development peers, and (2) the asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…A potential cohort study examining sex-specific associations of neonatal and childhood exposure to eight trace elements with the cognitive abilities of 296 school-age children reported similar results [24]. Multiple studies have indicated that elevated levels of Pb in the blood can impact the intelligence of children [8,25,26]. In multiple metal linear regression models, the negative correlation between urinary lead and children's intelligence was found to be non-significant in studies in Spain (urinary Pb median = 1.04 µg/L) [27] and Italy (urinary Pb median = 1.17 µg/L) [8,28].…”
Section: Discussionmentioning
confidence: 87%
“…A potential cohort study examining sex-specific associations of neonatal and childhood exposure to eight trace elements with the cognitive abilities of 296 school-age children reported similar results [24]. Multiple studies have indicated that elevated levels of Pb in the blood can impact the intelligence of children [8,25,26]. In multiple metal linear regression models, the negative correlation between urinary lead and children's intelligence was found to be non-significant in studies in Spain (urinary Pb median = 1.04 µg/L) [27] and Italy (urinary Pb median = 1.17 µg/L) [8,28].…”
Section: Discussionmentioning
confidence: 87%
“…The CBCL scale is a short, standardized questionnaire which was designed to identify social, behavioral, and emotional problems in children with ASD [ 28 ]. The CBCL scale consists of depression, somatic complaints, social withdrawal, aggression, defiant, compulsive, schizotypal, and poor interaction scores [ 20 ]. The scale was filled by children’s parents for more than half a year until the next by professionals based on the child's performance for almost half a year.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 57 behavioral traits of children with autism were included. It can be used for people between 2 months and 28 years of age [ 20 ]. Completed by the parents based on the child's performance at the time of the physical examination.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various reports on Cd concentrations in children with ASD are presented. Some documents have reported elevated levels of Cd in children with ASD compared to healthy ones [ [19] , [20] , [21] ], while other studies have shown no significant association between Cd levels and ASD occurrence [ [22] , [23] , [24] ]. Of the numerous literatures that have assessed the associations between Hg exposure and ASD, most studies have shown that Hg could be considered a risk factor for ASD [ 19 , 20 , 25 ].…”
Section: Introductionmentioning
confidence: 99%